Components of the mitochondrial cAMP signalosome - Monterisi, S; Zaccolo, M (Portland Press, 2017)
3′-5′-Cyclic adenosine monophosphate/protein kinase A (cAMP/PKA) signalling is activated by different extracellular stimuli and mediates many diverse processes within the same cell. It is now well established that in order to translate into the appropriate cellular function multiple extracellular inputs, which may act simultaneously on the same cell, the cAMP/PKA signalling pathway is compartmentalised. Multimolecular complexes are organised at specific subcellular sites to generate spatially confined signalosomes, which include effectors, modulators and targets of the pathway. In recent years, it has become evident that mitochondria represent sites of compartmentalised cAMP signalling. However, the exact location and the molecular composition of distinct mitochondria signalosomes and their function remain largely unknown. In this review, we focus on individual components of the cAMP/PKA signalling pathway at distinct mitochondria subdomains represented by the outer and inner mitochondrial membranes, the intermembrane space and the matrix, highlighting some of the questions that remain unanswered.